Reference interdisciplinary perspectives - Gundel, Jeanette K.; Hedberg, Nancy Ann. (Oxford : Oxford University Press, 2008)
These articles, written by leading scholars in linguistcs computational linguistics, philosophy and cognitive psychology examine reference from a number of disciplinary and interdisciplinary perspectives, informed by different research traditions and employing different methodologies.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Reference (Linguistics); Reference (Philosophy)